Fungal Pretreatment Of Wheat Straw And Its Effect On The Soda-Aq Pulps - Fatehi, Pedram; Ates, Saim; Ni, Yonghao (Aperta, 2009)
In this study, the effects of Ceriporiopsis subvermispora (C.S.) and Phlebia subserialis (P.S.) fungal pretreatments of wheat straw on the pulp and paper properties of soda-AQ pulps were investigated. The results showed that both fungal pretreatments enhanced delignification and carbohydrate degradation. Also, the P.S. pretreatment increased the brightness and decreased the kappa number and viscosity of pulps more than the C.S. pretreatment. Generally, the bulk, brightness, and tear index of papers increased by the fungal pretreatments, while the tensile and burst indices decreased at all refining levels applied. The C.S. pretreatment had more pronounced effect than the P.S. pretreatment on increasing the bulk and decreasing the tensile and burst indices. Furthermore, cationic-modified poly(vinyl alcohol), CPVA, was used as a dry strength additive to compensate for the loss in the strength properties. The results showed that, upon similar CPVA adsorption, the strength properties of the papers made of the C.S. pretreated fibers were improved more than those of the P.S. pretreated fibers. The application of CPVA on unrefined or refined fungal pretreated fibers showed the possibilities of decreasing the basis weight of papers to achieve the same tensile strength.